Mindanao's Showroom Industries - Gaspar, Karl (Kasarinlan: Philippine Journal of Third World Studies, 2007)
Review of Showcase of Underdevelopment: Fishes, Forests, and Fruits by Eduardo Tadem, Johnny Reyes, and Linda Susan Magno. Published by the Alternatives Resource Center, 1984, 208 pages.
Keywords: Mindanao; underdevelopment